2012
DOI: 10.1002/chem.201102902
|View full text |Cite
|
Sign up to set email alerts
|

One‐Handed Helical Screw Direction of Homopeptide Foldamer Exclusively Induced by Cyclic α‐Amino Acid Side‐Chain Chiral Centers

Abstract: Chiral cyclic α,α-disubstituted amino acids, (3S,4S)- and (3R,4R)-1-amino-3,4-(dialkoxy)cyclopentanecarboxylic acids ((S,S)- and (R,R)-Ac(5)c(dOR); R: methyl, methoxymethyl), were synthesized from dimethyl L-(+)- or D-(-)-tartrate, and their homochiral homoligomers were prepared by solution-phase methods. The preferred secondary structure of the (S,S)-Ac(5)c(dOMe) hexapeptide was a left-handed (M) 3(10) helix, whereas those of the (S,S)-Ac(5)c(dOMe) octa- and decapeptides were left-handed (M) α helices, both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
41
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 69 publications
0
41
1
Order By: Relevance
“…A right-handed (P) 3 10 -helix is induced in relatively shorter L-amino acid-based peptides having a high Aib content; however, a right-handed (P) α-helix is preferentially formed in relatively longer L-amino acid-based peptides having a low Aib content. [7] Besides Aib, we incorporated cyclic dAAs such as achiral 1-aminocyclopentanecarboxylic acid (Ac 5 c), [8,9] chiral (S,S)-1-amino-3,4-(dimethoxy)cyclopentanecarboxylic acid {(S,S)-Ac 5 c dOM }, [8][9][10][11] and (1S,3S)-1-amino-3-methoxycyclopentanecarboxylic acid {(1S,3S)-Ac 5 c OM } [12,13] into L-Leu-based heteropeptides -(L-Leu-L-Leu-dAA) n -as model peptides. The amino acid (S,S)-Ac 5 c dOM has two chiral centers exclusively at the side chain without a α-chiral center, and the (1S,3S)-Ac 5 c OM has chiral centers both at the α-carbon and at the side chain.…”
Section: Introductionmentioning
confidence: 99%
“…A right-handed (P) 3 10 -helix is induced in relatively shorter L-amino acid-based peptides having a high Aib content; however, a right-handed (P) α-helix is preferentially formed in relatively longer L-amino acid-based peptides having a low Aib content. [7] Besides Aib, we incorporated cyclic dAAs such as achiral 1-aminocyclopentanecarboxylic acid (Ac 5 c), [8,9] chiral (S,S)-1-amino-3,4-(dimethoxy)cyclopentanecarboxylic acid {(S,S)-Ac 5 c dOM }, [8][9][10][11] and (1S,3S)-1-amino-3-methoxycyclopentanecarboxylic acid {(1S,3S)-Ac 5 c OM } [12,13] into L-Leu-based heteropeptides -(L-Leu-L-Leu-dAA) n -as model peptides. The amino acid (S,S)-Ac 5 c dOM has two chiral centers exclusively at the side chain without a α-chiral center, and the (1S,3S)-Ac 5 c OM has chiral centers both at the α-carbon and at the side chain.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of unnatural amino acids, such as α,α-disubstituted amino acids (dAAs) or cyclized β-amino acids have been shown to enhance peptide helical structures. [5][6][7] To investigate the effects of the secondary structure of CPPs on their cell membrane permeability, we designed and synthesized novel CPP derivatives containing dAAs residues such as α-amino-isobutyric acid (Aib). 8) For example, the nonapeptides FAM-βAla-(L-Arg-L-Arg-Aib) 3 -NH 2 (1, FAM: 6-fluorescein), FAM-βAla-(L-Arg-D-Arg-Aib) 3 -NH 2 (2) and FAM-βAla-(D-Arg-D-Arg-Aib) 3 -NH 2 (ent-1) were synthesized, and their cell-penetrating ability were evaluated.…”
mentioning
confidence: 99%
“…Therefore, the de novo design of peptides that fold into well-defined helical structures has been attracted great interest of many chemists. Non-proteinogenic amino acids such as α,α-disubstituted α-amino acids, [1][2][3][4] cyclic β-amino acids, [5][6][7][8][9] and cross-linked side chains 10,11) are often utilized as tools for peptide-helix stabilization. In particular, α-aminoisobutyric acid (Aib) has been widely incorporated into short natural L-peptides to promote the formation and the stabilization of helical structures.…”
mentioning
confidence: 99%
“…12) Recently, we have reported that the introduction of Aib residues into the leucine (Leu)-based Lpeptide stabilized its right-handed (P) 3 10 -helix Boc-(L-Leu-L-Leu-Aib) 3 -OMe (1), 13) whereas the insertion of achiral Aib residues into alternating Leu-based LD-peptides stabilized their α-helices, but not their 3 10 -helices. Specifically, we reported that the nonapeptide Boc-(L-Leu-D-Leu-Aib) 3 -OMe (4) formed a (P) α-helix both in solution and in the crystalline state. 14,15) As part of our ongoing research, we investigated the influence of D-Leu residues on the helical structures of L-Leu-based nonapeptides.…”
mentioning
confidence: 99%
See 1 more Smart Citation